Development of the Guidelines Module in Counseling to Prepare Young Women on Facing Physical Change - Amelia Safitri; Mudjiran Mudjiran; Alizamar Alizamar (Global Econedu, 2019)
Self-preparation in dealing with physical changes is a necessity for young women, and lack of preparation will lead to several problems such as; anxiety, fear, timidity, sleeplessness, loss of appetite, and disruption of adult development. Self-preparation can be improved through information services provided by counselors using appropriate media and materials. The ADDIE model was used in this research and six experts were employed as subjects to validate service guidelines based on the display of laid down principles. Three counselors were on standby to test the use of the guidelines, and a total of thirty students were tested. The descriptive and inferential analysis with the Kendall coefficient (W) test were used to perform the examination. Therefore the result of the study shows that the prototype information service module can be used to prepare young women for physical changes during puberty.